ChemInform Abstract: Radical Beckmann Rearrangement and Its Application in the Formal Total Synthesis of Antimalarial Natural Product Isocryptolepine via C—H Activation. Issue 48 (10th November 2016) - Mahajan, Pankaj S.; Humne, Vivek T.; Tanpure, Subhash D.; Mhaske, Santosh B.
Abstract: The Beckmann rearrangement of ketoximes is mediated by ammonium persulfate‐dimethyl sulfoxide as a reagent under neutral conditions.